A review on different modes and methods for yielding a pentose sugar: xylitol. (March 2014) - Jain, Hansa; Mulay, Sanjyot
Abstract Xylitol, a five-carbon polyalcohol, holds a substantial place in the cure and prevention of a number of diseases. The foremost reason for its lesser usage in day-to-day practice is its cost. The method employed on large scale production of this polyol, i.e. chemical reduction, uses extensive machinery and expensive chemicals thus increasing the basic cost of the sugar. Yield of xylitol by other methods including fermentation and enzymatic production is far less than chemical reduction. We did a literature analysis and briefed out the various experiments carried out till date and concluded on the required studies for improving its production and lowering down its cost.